Yamato-791197: A lunar meteorite in the Japanese collection of Antarctic meteorites - Yanai, Keizo; Kojima, Hideyasu (1984)
P(論文) Antarctic meteorite Yamato-791197 has been identified and classified as an anorthositic regolith breccia; one of the rare meteorites that originated on the moon surface. The meteorite is remarkably similar to lunar highland regolith breccias in texture, mineralogy and chemical composition, but different from other meteorites, for instance polymict eucrites and howardites, in many respects. The specimen is almost completely covered with a thick dusty-gray fusion crust, and consists of many angular clasts and black to dark brown glassy matrix. The clasts, several mm across, are white, gray and black in color, and show a variety of textures including granulitic, gabbroic, diabasic and basaltic, and vitric (melted lithic). Most clasts have been shocked. The specimen also contains rare small glass spherules. Microprobe analyses show that feldspars range from An_<92.0> to An_<98.2>, pyroxenes : En_<18.0-83.1>Fs_<9.0-58.9>Wo_<1.7-44.1> and olivines : Fo_<13.6-92.1>. The FeO/MnO ratios of both pyroxenes and olivines of Yamato-791197 are lower than those of basaltic achondrites and are similar to those of lunar samples. departmental bulletin paper